HUBUNGAN ANTARA KONSUMSI TENAGA DAN KECEPATAN PEMBELAHAN - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Eighteen logs of several wood species were used as material for the above study. Each log was sawn on a 44 inch Band Headrig with automatic carriage. Specifications of machine and sawblade used are listed in table 2. Sawing velocity was determined by the ampleness of cutting area per unit cutting time on every sawing line. Whereas the power consumption was detected by the ampere-meter set on the motor electric circuit. The ampere value is then transformed to the power consumption unit (Watt-second/cm2). The result of statistical calculation revealed a close relationship between power consumption and sawing velocity. Power consumption can be estimated from the sawing velocity in accordance with the regression equation : Y = 82.97 -0.118 X. The correlation is negative and almost perpect (correlation coefficient r = - 0.908). This means that, power consumption will increase if sawing velocity decreases, and vice versa.